Peran Pendidikan Pancasila dalam Pembentukan Karakter Mahasiswa: Suatu Upaya Membangun Etika dan Moral - Furnamasari, Yayang Furi; Putri, Ajeng Adistya; Syamsiah, Dinda Nur; Amanatin, Ifah; Mufidah, Kayla Rahma; Afifah, Linda Dwi Ayuni; Syahroni, Rendi Herman; Rahayu, Rina; Zikri, Shiva Aqila (Indo-MathEdu Intellectuals Journal, 2024)
Pancasila education in universities has an important role in shaping the character of students with strong ethics and morals. Through understanding and applying the values of Pancasila, students are expected to develop a strong character, responsibility, and integrity. The purpose of the study is to gain a deep understanding of the role of Pancasila education in the formation of student character as well as efforts to build strong ethics and morals. This research is qualitative research through literature study. Literature collection is done by collecting relevant sources such as scientific journals, books, articles, and other related documents. The main source in this research is scientific articles from research published through the Google Scholar website. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The results of data analysis show that Pancasila education is needed as a basic foundation to form ethics and morals, which are tough, where activities in the university environment include habits that can encourage students to behave according to what is contained in Pancasila values